2015
DOI: 10.1111/ans.13435
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of laparoscopic surgery in intussusception?

Abstract: Laparoscopic intervention is meaningful in approximately 50% of children requiring a surgical reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Similar results have been reported in recent studies. 3,[16][17][18][19] The patients in this study underwent reduction 1.97 times (mean) before surgery, and a lead point was found in 8.1% of the patients. Wei et al reported a 13% conversion rate from laparoscopic procedure to laparotomy, which was more common in cases with a long intussusception.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Similar results have been reported in recent studies. 3,[16][17][18][19] The patients in this study underwent reduction 1.97 times (mean) before surgery, and a lead point was found in 8.1% of the patients. Wei et al reported a 13% conversion rate from laparoscopic procedure to laparotomy, which was more common in cases with a long intussusception.…”
Section: Discussionmentioning
confidence: 78%
“…Only pathologic lead point was a risk factor for bowel resection in this study, which is consistent with the findings in recent reports. 8,18 Overall, we believe that laparoscopic surgery is worth attempting in patients who have had symptoms for more than 48 h and who do not show peritonitis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study by Houben et al reported a high conversion rate (46%) to OS. 22 However, in successful cases, fewer hospitalization days have been reported. In that study, the reason for converting LS to OS was reported as rigid non-manipulative intussusception in seven cases, small abdominal cavity volume for maneuvering and manipulation in four cases, and in two cases, the impossibility of evaluating tactile response with intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…This success rate of laparoscopy is comparable to other recent studies with good results. 4,7 Laparoscopic treatment of intussusception in children is technically feasible with successful outcomes if the patient shows no signs of peritonitis or severely distended abdomen. Although the pathologic lead point can make the reduction impossible, the need for bowel resection with conversion to open surgery can be decided according to the presence of a lead point or the failure of reduction after a laparoscopic trial of reduction of intussusceptum.…”
mentioning
confidence: 99%